Systematic Review on the Functional Status of Elderly Hip Fracture Patients using Katz Index of Activity of Daily Living (Katz ADL) Score - MA, Sharkawi; SM, Zulfarina; SMZ, Aqilah-SN; NM, Isa; AM, Sabarul; AS, Nazrun (IIUM Medical Journal Malaysia, 2016)
Hip fractures cases are common in elderly population. After a hip fracture, around 80% of patients were unable to carry out at least one independent activity of daily living (ADL). This review attempted to provide an evidence-based literature on ADL of elderly hip fracture patients. A computerised literature search using Medline (OVID) and Scopus databases were conducted to identify relevant studies on ADL of elderly hip fracture patients that was assessed with Katz ADL score. Only articles that fulfilled the inclusion criteria were included in this review. Initial search identified 314 potentially relevant articles but after careful screening, only 5 full-text articles were selected for the present review. Three studies showed an increase dependent level of the patients’ ADL after hip fractures. Two studies showed not more than half of the patients were unable to regain their pre-fracture ADL level after one year of hip fracture incidence. Feeding/eating showed the highest independent activity while bathing was the lowest independent activity among patients. In conclusion, elderly hip fracture patients have declined ADL with the risk that they may never regain their pre-fracture ADL level.